Choice Hygiene for “Consumer Neuroscientists”? Ethical Considerations and Proposals for Future Endeavours - Christensen, Julia F.; Farahi, Fahimeh; Vartanian, Meghedi; Yazdi, Sina H. N. (Frontiers in Neuroscience, 2022)
The use of psychological and neuroscientific methods for marketing research is not always aligned with the principles of ethical research practice. Problematic points are (i) the use of deception, (ii) failing to safeguard individual's dignity, (iii) inadequate use of methods, and (iv) failing to safeguard effects on the environment. Some neuromarketing endeavours have passed from informing consumers about available options, to helping to market as many products to consumers as possible. Needs are being engineered, using knowledge about the human brain to increase consumption further, regardless of individual, societal and environmental needs and capacities. In principle, the ground ethical principle of any scientist is to further individual, societal and environmental health and well-being with their work. If their findings can be used for the opposite, this fact must be part of the scientist’s considerations before engaging in such research and to make sure that the risks for misuse are minimized. Against this backdrop, we provide a series of real-life examples and a non-exhaustive literature review, to discuss in what way some practices in the neuromarketing domain violate the Helsinki Declaration of Experimentation with Human Subjects. This declaration was set out to regulate biomedical research, but has since its inception been applied internationally also to behavioural and social research. We illustrate, point by point, how these ground ethical principles could be applied also to the neuromarketing domain. Indisputably, the growth in consumption is required due to current prevalent economical models. Thus, in the final part of the paper, we discuss how alternative models may be promotable to a larger public, aided by more ethical marketing endeavours, based on neuroscientific discoveries about the human brain. We propose this as a more philosophical question, a point of discussion for the future, to make neuromarketing as a discipline fit for the future, respecting the ethical implications of this research.